Smith–Purcell radiation controlled by the transmission characteristics and quality factor of a layer - Zhang, Ping; Shu, Jing; Dong, Yin; Zhang, Shuhe; Cao, Xinxin; Wang, Xiaosong; Yang, Shengpeng; Liang, Bingyang; Zheng, Yuan; Wang, Shaomeng; Gong, Yubin (Journal of applied physics, 2023)
Photonic crystal structures have attracted significant attention because of their ability to confine light, especially outgoing waves in a bandgap. In this study, we investigate a layer that can control the Smith–Purcell radiation. The results show that transmission characteristics and quality factor of a 1D photonic crystal can narrow the radiation spectrum and enhance the radiation intensity. From another perspective, the entire structure can be treated as a composite grating, the radiation spectra of which are obtained by theoretical calculations and agree with that from the analysis based on the role of the 1D photonic crystal. Therefore, it can be concluded that the radiation from a composited structure can be simplified by the radiation controlled by the 1D metal photonic crystal, and it provides a fast way to reshape the radiation spectra by designing the transmission characteristic and quality factor of the photonic crystal. Furthermore, a layer with special transmission characteristics and quality factor above a reflection grating can be used to achieve coherent and tunable Smith–Purcell radiation, which is significant for the development of band-controllable light or terahertz radiation sources.